Recent trends in the Studies of Environmental Speciation and Ecological Consequence Regarding Analysis in Soil, and Sediment Samples: A Review - Melegy, A.; El-Shamy, A. M. (Journal of Environmental Accounting and Management, 2026)
Because an element’s chemical species affects toxicity, environmental mobility, and bioavailability, speciation analysis is vital in contemporary analytical chemistry. In recent years, attempts have been undertaken to identify not just components but also their species. This review highlights the latest methodologies and techniques in environmental analytical chemistry to address this tendency. Different sample treatment processes are introduced and explained, with an emphasis on employing modern nanomaterials and novel solvents in the solid phase and liquid-liquid microextraction, and on speciation analysis. An in-depth examination of experimental methods for separating and quantifying metal and metalloid species, from chromatography to electrochemistry, is also offered. This research emphasizes the greenness of these achievements, analyzing their green chemistry and environmental effects. Identifying and quantifying an element’s chemistry is called "element speciation". Because an element’s toxicity depends on its chemical form, specification analysis is a popular issue in environmental research. Trace element levels in environmental samples have been heavily studied. Total elemental composition no longer indicates toxicity in risk assessment. Speciation analysis measures the relative concentrations of an element’s physicochemical forms in a sample. Physicochemical forms include gaseous, solid, and liquid substances. It’s frequently required to specialize when studying the damaging and life-saving effects of trace elements.